Desarrollo de las economas regionales - Rios Medina, Mike Bryam (2019)
The development of the regions is thanks to the own resources of each region and the _x000D_ injection of state and private capital, promoting our economy; inside of this conception La _x000D_ Libertad region has a great participation and is a good representative of economic _x000D_ development , in its majority this is based on its agropecuaria activity. _x000D_ We are one of the regions with the best productive lands . we can cultive sugar cane, this _x000D_ product with a great commercial takeoff, becouse our distillate extra-thin gives the quality _x000D_ of international export to our alcohol and other derivaties .We also produce asparagus that _x000D_ has become popular in the United States in the last years, as well as palta, artichoke, _x000D_ yellow hard corn ,the last products with a highest reception in Europe; the product has a _x000D_ growing export in the first trimester of the year was the red pepper for the Argentine _x000D_ market, becouse the quality of our product produced by having a good color, aroma and _x000D_ shape. _x000D_ The economic development of the economy of the La Libertad region has been favored by _x000D_ one of the most ambitious projects in all of Latin America, the CHAVIMOCHIC project, _x000D_ that transport the waters of the Santa River for the irrigation of the valleys and intervals of _x000D_ Chao, Vir, Moche and Chicama; actuallly has been in the third stage.